If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 7 = 3 + -1x Reorder the terms: 7 + x = 3 + -1x Solving 7 + x = 3 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 7 + x + x = 3 + -1x + x Combine like terms: x + x = 2x 7 + 2x = 3 + -1x + x Combine like terms: -1x + x = 0 7 + 2x = 3 + 0 7 + 2x = 3 Add '-7' to each side of the equation. 7 + -7 + 2x = 3 + -7 Combine like terms: 7 + -7 = 0 0 + 2x = 3 + -7 2x = 3 + -7 Combine like terms: 3 + -7 = -4 2x = -4 Divide each side by '2'. x = -2 Simplifying x = -2
| 2y+2+10y-2=90 | | 1Dwight+2x= | | 3(m-3)=0 | | 7m-2=0 | | 11x-5x+6x=168 | | -73+29= | | 2x+11=3x+11 | | 7ab(a+5b+ab-6^2)= | | 6z+18=z | | 2(4a+5)=1.8a-3 | | 2(5-4x)=-46 | | 29-9x=-5(7x+2)-5(-4-5x) | | 2x+11=2x-19 | | -8m-24=24 | | 5-2(y-5)=267 | | y+6n=6n+5 | | 40x=60y | | 4z+11=2z+7 | | 5y+6=-y+24 | | 42-14x=-5(6x+2)-5(-8-3x) | | 2(3a+1)=12+2(4a+3) | | 8-5x-4=-6x+6 | | 3m-4=20 | | 25*x^2-16*x^2= | | Y+14=10 | | x^0+1=0 | | 14x-12+30=4 | | 8z-9=90 | | 2z+y=4z+11 | | z=6z+18 | | 8z-9=1z+9 | | (4x-2)=(4x+10) |